2006
DOI: 10.1093/jhered/esj009
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Time to Flowering in Chickpea in a Short-Season Temperate Environment

Abstract: Time to flowering is central in determining the adaptation and productivity of chickpea in short-season temperate environments. We studied the genetic control of this trait in three crosses, 272-2 x CDC Anna, 298T-9 x CDC Anna, and 298T-9 x CDC Frontier. From each cross, 180 F2 plants and parents were evaluated for time to flowering under greenhouse conditions. In summer 2004, multiple generations including P1, F1, P2, F2, and F2:3 (also called MG5) were evaluated for time to flowering under field conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 18 publications
5
45
1
2
Order By: Relevance
“…CDC Frontier typically initiated abortive flower buds at nodes 16 to 20 prior to the formation of perfect flowers regardless of photoperiod, but the number of abortive buds was greater under SD. We observed that F1 populations derived from ICCV 96029 crosses were entirely late flowering under SD, whereas early flowering was recessive in the F2 populations derived from a range of crosses involving ICCV 96029 in our breeding program, consistent with previous reports of recessive earlyflowering phenotypes in segregating populations derived from ICCV 96029 (Gumber and Sarvjeet, 1996;Or et al, 1999;Kumar and van Rheenen, 2000;Anbessa et al, 2006).…”
Section: Qtl Analysis Reveals a Major Flowering Time Locus On Ca5supporting
confidence: 90%
“…CDC Frontier typically initiated abortive flower buds at nodes 16 to 20 prior to the formation of perfect flowers regardless of photoperiod, but the number of abortive buds was greater under SD. We observed that F1 populations derived from ICCV 96029 crosses were entirely late flowering under SD, whereas early flowering was recessive in the F2 populations derived from a range of crosses involving ICCV 96029 in our breeding program, consistent with previous reports of recessive earlyflowering phenotypes in segregating populations derived from ICCV 96029 (Gumber and Sarvjeet, 1996;Or et al, 1999;Kumar and van Rheenen, 2000;Anbessa et al, 2006).…”
Section: Qtl Analysis Reveals a Major Flowering Time Locus On Ca5supporting
confidence: 90%
“…Dias para florescimento em grão de bico é um dos maiores componentes da adaptação ambiental, particularmente quando a estação de cultivo é restringida por fatores climáticos como estresse hídrico e altas temperaturas (Or et al, 1999). Essa característica é também influenciada pela estação de cultivo, latitude, altitude, foto-período e temperatura (Anbessa et al, 2006). Em outras avaliações de genótipos de grão de bico conduzidas sob 12/18 horas de regime de luz mostraram variações entre 27 e 43 dias para florescimento (Anbessa et al, 2006), revelando grande diversidade entre os genótipos avaliados.…”
Section: Resultsunclassified
“…Essa característica é também influenciada pela estação de cultivo, latitude, altitude, foto-período e temperatura (Anbessa et al, 2006). Em outras avaliações de genótipos de grão de bico conduzidas sob 12/18 horas de regime de luz mostraram variações entre 27 e 43 dias para florescimento (Anbessa et al, 2006), revelando grande diversidade entre os genótipos avaliados. O período de floração no grão de bico exerce um efeito importante na manifestação do potencial genético da espécie (Mbarek et al, 2009).…”
Section: Resultsunclassified
“…A greater action of the additive genetic effects was evidenced in the traits mean weight of seeds and total number of pods per plant. The understanding of the relative contributions of the genetic and environmental components in variance control of interest traits is a crucial aspect of breeding programs (Anbessa et al, 2006).…”
Section: Discussionmentioning
confidence: 99%